Non-melt processible fluoroplastics : the definitive user's guide and databook - Ebnesajjad, Sina (Plastics Design Library, 2000)
Focuses on homofluoropolymer polymerization and part fabrication technology. Discuses a range of issues surrounding the manufacturing of the monomer. Polymer, fabrication, end-use, safety, and disposal are also covered.
Keywords: Fluoropolymers -- Handbooks, manuals, etc.; elektronické knihy; electronic books